Inflating Shallow Plumbing System of Bezymianny Volcano, Kamchatka, Studied by InSAR and Seismicity Data Prior to the 20 December 2017 Eruption - Mania, René; Cesca, Simone; Walter, Thomas R.; Koulakov, Ivan; Senyukov, Sergey L. (Frontiers in Earth Science, 2021)
Explosive eruptions are foreshadowed by movement and accumulation of magma in the surrounding rocks. These movements are happening at and beneath the volcano, in the so called plumbing system, and are detectable by modern sensors, allowing analyzing and interpreting eruption precursors. Nevertheless, the chronology and location of earthquakes or surface deformation is often complex and inconclusive, illustrating the lack of knowledge of the plumbing system. Insights into the cause-effect relationship between ground deformation, seismicity, and volcanic degassing is crucial to enhance the volcano monitoring, but such detailed observations of magma migration are often rare. Using a unique station network and the "lucky" occurrence of one of the largest eruptions, we here characterize degassing, surface deformation, and seismic data recorded at Bezymianny volcano, Russia. We observe near-continuous enhanced low-frequency seismicity accompanied by strong degassing activity that started to emerge three months before the eruption, without clear deformation signals. During short-term uplift of the volcano, we discover significant very-low-frequent seismic (tremors) activity potentially related to processes within the uppermost parts of the volcano. We set up a theoretical model to explain the sequence of events including gas-rich magma migration and accumulation leading to the surface deformation. Additionally, we compare the evolution of tremor activity and atmospheric pressure indicating a potential relationship. Our results further promote the significance of the combined analysis of deformation and seismic data for volcano monitoring.